Network Performance and Security Analysis of Software Defined Networking - Haggag, Ayman; Hanafy, Dalia (International Journal of Scientific Research in Computer Science and Engineering, 2021)
Software-Defined Networks (SDN) have gained a great interest among both academic and industry professionals. As this direction has not yet reached maturity, there is still a lot of research needed to help make it a dominant industrial technology choice. This paper presents the current status and identifies the future trends of SDN networks. Several SDN network topologies are implemented using Mininet and various benchmarking tools are applied for performance evaluation. Simulation results show that the global view of the SDN controller greatly enhances network performance at heavy network traffic loads and allows for efficient load balancing. On the other hand, the SDN controller represents a single point of attack vulnerability that requires special security precautions against DoS and DDoS attacks.